Implementasi Strategi Pembelajaran PAI Kontekstual dalam Membentuk Karakter Sosial Peserta Didik - Sania Junila; Hazizah Delpina; Gusmaneli . (CV. ITTC INDONESIA, 2026)
Islamic Religious Education (PAI) learning, which has so far focused more on textual aspects and memorization, is considered not yet effective in building students’ social character in a real sense. This study aims to investigate how contextual PAI learning strategies are implemented and how significant their influence is on the formation of students’ social character. The research method was conducted using a descriptive qualitative approach through observation, interviews, and document analysis. The findings show that the consistent application of the seven elements of contextual learning, namely constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment, can develop attitudes of mutual help, empathy, tolerance, and social responsibility among students. The success of the implementation is strongly influenced by the teacher’s ability to relate PAI materials to students’ daily lives, as well as support from a conducive school environment. This study recommends strengthening the competence of PAI teachers in designing context-based learning as a strategic step in creating a generation that is not only intellectually intelligent, but also morally upright and socially caring.